Діагностика патології серцево-судинної системи у хворих на гіпотиреоз - Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2010)
The article provides an diagnostic algorithm of the cardiovascular system dysfunction, according to research of various parts of hemodynamics, including microcirculation and activity of tissue oxygenation in patients with hypothyroidism depending on their age. It was shown that the lesions have some age peculiarities. Common to patients of all ages is the existence of a syndrome of myocardial hypokinesia, systolic dysfunction, a violation of microcirculation and decrease of tissue oxygenation activity. It was determined that the achievement of euthyroidism in patients improves hemodynamic parameters but does not provide their full normalization.